#8
2x+3x+4x = 63
x = 7
So, the actual quantities are
14:21:28
#9
3ab/27ab = 1/9
So, A,B,E are the equivalent ratios. D doesn't get rid of the a,b stuff.
Odd how you could get B and E right, but miss A and pick D...
#10
B and D only
8. Abby, Ingrid, and John are sharing a bag of candy in the extended ratio 2:3:4. If there are sixty three candies in the bag, then how many will Ingrid get?
A. 7
B. 14***
C. 21
D. 28
9. Which of the following are equivalent to the ratio 3ab:27ab? Select all that apply.
A. 1:9
B. 9a:81a***
C. a:b
D. a:3b***
E. 2:18***
F. 3b:27a
10. Which of the following are equal to the ratio (2 x-6) : (6x-4)?
A. -2 : 1
B. x - 3: 3x - 2***
C. 3x : x
D. (4x-12) : (12x - 8)
E. x - 1 : x - 2***
Please check and help :( I think I'm wrong on at least half but I have no idea
8 answers
8.
A = Abby's part
I = Ingrid's part
J = John's part
There are sixty three candies in the bag.
This mean:
A + I + J = 63
A / I / J = 2 / 3 / 4
This mean :
A / I = 2 / 3
I / J = 3 / 4
so:
A / I = 2 / 3 Multiply both sides by I
A = 2 I / 3
A = ( 2 / 3 ) I
I / J = 3 / 4 Multiply both sides by 4
4 I / J = 3 Multiply both sides by J
4 I = 3 J Divide both sides by 3
4 I / 3 = J
J = 4 I / 3
J = ( 4 / 3 ) I
Replace this value in equation:
A + I + J = 63
( 2 / 3 ) I + I + ( 4 / 3 ) I = 63
( 2 / 3 ) I + ( 3 / 3 ) I + ( 4 / 3 ) I = 63
( 9 / 3 ) I = 63
3 I = 63 Divide both sides by 3
I = 63 / 3 = 21
9.
3 a b : 27 a b = 3 a b : ( 9 * 3 a b ) = ( 3 a b : 3 a b ) * 1 : 9 = 1 * 1 : 9 = 1 : 9
10.
( 2 x - 6 ) : ( 6 x - 4 ) =
2 * ( x - 3 ) : [ 2 * ( 3 x - 2 ) ] =
(2 : 2 ) ( x - 3 ) : ( 3 x - 2 ) =
1 * ( x - 3 ) : ( 3 x - 2 ) =
( x - 3 ) : ( 3 x - 2 )
A = Abby's part
I = Ingrid's part
J = John's part
There are sixty three candies in the bag.
This mean:
A + I + J = 63
A / I / J = 2 / 3 / 4
This mean :
A / I = 2 / 3
I / J = 3 / 4
so:
A / I = 2 / 3 Multiply both sides by I
A = 2 I / 3
A = ( 2 / 3 ) I
I / J = 3 / 4 Multiply both sides by 4
4 I / J = 3 Multiply both sides by J
4 I = 3 J Divide both sides by 3
4 I / 3 = J
J = 4 I / 3
J = ( 4 / 3 ) I
Replace this value in equation:
A + I + J = 63
( 2 / 3 ) I + I + ( 4 / 3 ) I = 63
( 2 / 3 ) I + ( 3 / 3 ) I + ( 4 / 3 ) I = 63
( 9 / 3 ) I = 63
3 I = 63 Divide both sides by 3
I = 63 / 3 = 21
9.
3 a b : 27 a b = 3 a b : ( 9 * 3 a b ) = ( 3 a b : 3 a b ) * 1 : 9 = 1 * 1 : 9 = 1 : 9
10.
( 2 x - 6 ) : ( 6 x - 4 ) =
2 * ( x - 3 ) : [ 2 * ( 3 x - 2 ) ] =
(2 : 2 ) ( x - 3 ) : ( 3 x - 2 ) =
1 * ( x - 3 ) : ( 3 x - 2 ) =
( x - 3 ) : ( 3 x - 2 )
Thank you guys!
Remark :
1 * ( x - 3 ) : ( 3 x - 2 ) =
( x - 3 ) : ( 3 x - 2 )
4 / 4 = 1 so :
( 4 / 4 ) * ( x - 3 ) : ( 3 x - 2 )
4 * ( x - 3 ) : [ 4 * ( 3 x - 2 ) ] =
( 4 x - 12 ) : ( 12 x - 8 )
Question 10
Answers B and D
1 * ( x - 3 ) : ( 3 x - 2 ) =
( x - 3 ) : ( 3 x - 2 )
4 / 4 = 1 so :
( 4 / 4 ) * ( x - 3 ) : ( 3 x - 2 )
4 * ( x - 3 ) : [ 4 * ( 3 x - 2 ) ] =
( 4 x - 12 ) : ( 12 x - 8 )
Question 10
Answers B and D
The entire Practice test- in order 1-10
B
C
D
C
D
A
C
C
A-B-E
B-D
B
C
D
C
D
A
C
C
A-B-E
B-D
Thanks Mr.RightGuys
@Mr.RightGuy 100% thanks
what grade is this for